2019
DOI: 10.1080/09546553.2018.1559836
|View full text |Cite
|
Sign up to set email alerts
|

Better the Devil You Know? How Fringe Terrorism Can Induce an Advantage for Moderate Nonviolent Campaigns

Abstract: Fringe terrorism is common during nonviolent campaigns. We examine how this can modify the strategic environment between dissident groups and the state in ways that present both challenges and opportunities to moderate factions. Terrorism is intended to promote violent escalation in a conflict, but we argue that fringe terrorist activities in a nonviolent campaign under certain conditions can induce an advantage for well-organized moderate factions. The risk of escalation following terrorism can give the gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is further unclear why Anisin chose those two new classifications and decided against using already existing categories. Among others, there is research on the role of fringe terrorism in nonviolent campaigns, which is distinctively different from unarmed violence (Belgioioso et al, 2019). As armed actors are in fact sometimes part of otherwise nonviolent campaigns, as pointed out by Pinckney (2016), there seems to be insufficient justification to treat unarmed violence as a category of anti-regime campaigns.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…It is further unclear why Anisin chose those two new classifications and decided against using already existing categories. Among others, there is research on the role of fringe terrorism in nonviolent campaigns, which is distinctively different from unarmed violence (Belgioioso et al, 2019). As armed actors are in fact sometimes part of otherwise nonviolent campaigns, as pointed out by Pinckney (2016), there seems to be insufficient justification to treat unarmed violence as a category of anti-regime campaigns.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…A radical flank is defined as a group that is more radical than the movement's moderate body in regards to their (1) tactical choices, (2) political demands, or (3) beliefs, choice of words, and openness for compromise (Chenoweth & Schock, 2015). So far, researchers have not yet reached a consensus if the presence of a radical flank has mostly positive or negative effects for the movement (Belgioioso et al, 2021;Haines, 2013). Generating public support is a key goal of social movements, and is especially relevant for environmental movements.…”
Section: Highlightsmentioning
confidence: 99%
“…Several studies identified favorable effects: Empirical evidence focusing on the out come of campaign progress identified positive RFEs (Belgioioso et al, 2021;Tompkins, 2015), and an insignificant RFE (Chenoweth & Schock, 2015). Furthermore, a radical campaign against fossil fuels had a positive influence on the media framing of the climate debate (Schifeling & Hoffman, 2019).…”
Section: The Need For a Psychological And Experimental Perspectivementioning
confidence: 99%
“…Scholars have not yet adopted a uniform set of indicators to evaluate these relationships. Within the existing literature, violent flanks variably include armed, unarmed, or unspecified forms of violence, including organized armed rebellion (Barrell 1993, Chenoweth & Schock 2015, Belgioioso et al 2021, unarmed collective violence (Kadivar & Ketchley 2018, Anisin 2020, riots (Case 2021), or a combination of these.…”
Section: Violent Flank Effects: Positive Negative or Null?mentioning
confidence: 99%
“…The degree to which violence within these mass movements influences their outcomes is the subject of lively debate in the field. Some argue that riots, unarmed collective violence, or even armed violence can help an otherwise nonviolent resistance movement to achieve its goals (Bray 2017, Kadivar & Ketchley 2018, Enos et al 2019, Rossdale 2019, Thaler 2019, Anisin 2020, Belgioioso et al 2021, Case 2021. Others suggest that such activities undermine the appeal of mass movements to the public and alienate key allies (Thomas & Louis 2014, Chenoweth & Schock 2015, Thompkins 2015, Adelman et al 2017, Huet-Vaughn 2017, Wantchekon & García-Ponce 2017, Simpson et al 2018, Muñoz & Anduiza 2019, Orazani & Leidner 2019, Wasow 2020, Abbs & Gleditsch 2021, Steinert-Threlkeld et al 2022.…”
Section: Introductionmentioning
confidence: 99%